The fate of particles in the dynamical environment around Kuiper-Belt object (486958) Arrokoth - Amarante, A.; Winter, O. C. [UNESP] (Springer Nature, 2022)
The contact binary Kuiper-Belt object (486958) Arrokoth, targeted by the New Horizons mission, has a unique slope pattern, which is a result of its irregular bilobate surface shape and high spin period. Thus, some peculiar topographic regions on its surface are predisposed to lose or accumulate material, as a long circular depression feature, an impact crater called Maryland, on its small lobe. The equilibrium points of Arrokoth are also directly related to the structure of the environment near these surface features. In this work, we performed numerical simulations around Arrokoth to explore the fate of particles close to equilibrium points and their dynamical connection with its surface features. Our results suggest that most of these particles in a ring inside Arrokoth’s rotational Roche lobe fall near the equatorial region of the Maryland impact crater or close to the Bright spots area on the large lobe. Also, particles in a spherical cloud orbiting Arrokoth accumulate preferentially near low–midlatitude regions close to the longitudes of the Maryland crater and the Bright spots area. In contrast, a few particles will fall in regions diametrically opposite to them, as in the LL_Term boundary on the large lobe. High latitudes are those more empty of impacts, as in polar sites. In addition, particles larger than a couple of micrometers are not significantly perturbed by solar radiation pressure in the environment around Arrokoth.
Keywords: Celestial mechanics; Kuiper-Belt objects: individual, (486958) Arrokoth; Methods: numerical; Software: development; Software: simulations